ANALISA NILAI TEGANGAN PATAH RANTAI JENIS ROLLER AKIBAT ADANYA DEFORMASI - Darmadi, Herry; Muttaqin, Maraghi; Paranita, Darni; Simbolon, Tommy Frans (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
The chain is a series of links or rings that are connected or fixed so that they form vertically. Chains are used to move luggage or as a substitute for additional strength. One of the most commonly used chains is made of the hardest metal, steel. One is a chain roller mounted on an empty coil conveyor. This conveyor serves to carry empty coils to the shelter. The chain also plays a role in the distribution of materials from one place to another to make it more efficient. In this study, the authors tested five chain materials to determine the breaking stress and the factors that influence chain breaking. After the authors tested the steel chain material, the value of the chain tensile stress (σB), based on the test results after averaged was 880 Kgf/cm2, and the chain fracture stress (σF) after averaged was 764. is Kgf/. the average strain on the chain (ԑ) is 8.9°. Causes of chain breaks are overload, fatigue, improper heat treatment, improper design and manufacture, and lack of maintenance.